2015
DOI: 10.1007/s40264-015-0370-0
|View full text |Cite
|
Sign up to set email alerts
|

Tools for Assessing Potential Significance of Pharmacist Interventions: A Systematic Review

Abstract: The majority of tools focused primarily on assessing clinical aspects and failed to detect comprehensive impacts. The heterogeneity of tools and assessment processes hindered our ability to synthesize the results of evaluations. Limited results for their validity and reliability cast doubt on the credibility of this methodology for justification of the value of PIs. Recommendations for development of tools with optimal theoretical, pragmatic, and psychometric properties are proposed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 139 publications
0
27
0
Order By: Relevance
“…Hence, using clinical significance categorization systems as assessment methods does not seem robust and is most likely highly dependent on the choice of individual raters. This is supported by a review by Vo et al, who found limited results for the validity and reliability of tools for assessing the potential significance of pharmacist interventions [ 82 ]. Consequently, using a clinical significance rating as a method to prioritise DRP categories does seem suboptimal.…”
Section: Discussionmentioning
confidence: 70%
“…Hence, using clinical significance categorization systems as assessment methods does not seem robust and is most likely highly dependent on the choice of individual raters. This is supported by a review by Vo et al, who found limited results for the validity and reliability of tools for assessing the potential significance of pharmacist interventions [ 82 ]. Consequently, using a clinical significance rating as a method to prioritise DRP categories does seem suboptimal.…”
Section: Discussionmentioning
confidence: 70%
“…This has led to the reliance on key performance indicators to track interventions in many institutions. [8][9][10] It is currently unknown which pharmacist interventions are likely to be most impactful in the current pandemic; however, published recommendations have promoted interventions ranging from medication stewardship to coordination of laboratory timing to telehealth visits, when feasible. 11,12 Operational pharmacy services will also be impacted, and pharmacists and technicians will have to be adaptable to the shifts in medication needs that will accompany the influx of critically ill patients.…”
mentioning
confidence: 99%
“…We used a new validated tool to assess the clinical impact of PIs. 19 The CLEO tool has been recently created according to different scales available in the literature 24 and provided suitable inter-rater and intrarater reliabilities. This CLEO tool was used to assess clinical impact of PIs on injectable antineoplastic prescriptions in a French Hospital Chemotherapy Preparation Unit 33 and was translated and validated in a German version.…”
Section: Discussionmentioning
confidence: 99%